EFFECTIVENESS OF PERINEAL PELVIS REHABILITATION COMBINED WITH BIOFEEDBACK AND RADIOFREQUENCY DIATHERMY (RDF) IN ANORECTAL FUNCTIONAL PAIN SYNDROMES ASSOCIATED WITH PARADOXICAL CONTRACTION OF THE LEVATOR ANI MUSCLES. A PROSPECTIVE STUDY - Luigi BRUSCIANO; Antonio BRILLANTINO; Luigi FLAGIELLO; Marianna PENNACCHIO; Claudio GAMBARDELLA; Francesco Saverio LUCIDO; Alessandra PIZZA; Salvatore TOLONE; Gianmattia DEL GENIO; Ludovico DOCIMO (Arquivos de Gastroenterologia, 2023)
ABSTRACT Background: Anorectal functional pain syndrome, also called chronic proctalgia, represents a neglected clinical entity and often confused with other syndromes such as vulvodynia or acute proctalgia. It is a very often disabling disease with a consequent significant negative impact on the patient’s quality of life. Chronic proctalgia, in many patients, is secondary to the paradoxical contraction of the pelvic floor and associated with a dissynergy between the thorax-abdomen and the pelvic floor. To improve symptoms in functional anorectal pain syndromes, various rehabilitation techniques are used with the aim of promoting relaxation of the pelvic floor; however, to improve defecatory dynamics in patients with levator ani syndrome, only biofeedback has shown efficacy in a randomized study. The aim of this work is to evaluate whether a rehabilitation protocol with manometric biofeedback and radiofrequency diathermy (mt100 Fremslife emotion Tecar) reduces pain and paradoxical contraction of the levator ani and improves the quality of life in patients with anorectal pain syndromes. functional. Methods: This was a prospective study on 30 patients (20 women and 10 men) with anorectal functional pain syndrome and paradoxical contraction of the pelvic floor enrolled at the UOC of General, Minimally Invasive, Oncological and Obesity Surgery of the AOU “Luigi Vanvitelli” of Naples, Italy, from September 2021 to May 2022. All patients were evaluated with a coloproctological specialist visit followed by anorectal manometry and evaluation of altered clinical physiatric parameters (Brusciano Score). The protocol consisted of 10 rehabilitation sessions of the pelvic floor once a week and lasting approximately 45 minutes. During the sessions the patients were subjected to diathermy / radiofrequency treatment (10 minutes) with a static resistive electrode on the diaphragm, during which they were required to breathe diaphragmatically and to become aware of the perineal muscles, under the supervision of a physiotherapist; followed by application of diathermy with static capacitive (5 minutes) and resistive (10 minutes) electrode at the lumbar level. This was followed by the use of manometric biofeedback (15 minutes of tonic / phasic exercises) in order to instruct the patient on the reflex mechanism to obtain a voluntary relaxation of the external anal sphincter. The variables evaluated were Pain (VAS 0-10) and the questionnaire on the impact of colorectal and anal pathologies on the quality of life (CRAIQ-7) at the beginning, after 3 months and at the end of the treatment. Results: After 10 weeks, the rehabilitation treatment combined with diathermy and manometric biofeedback proved effective in the short term with a reduction in the scores of the Vas scale and CRAIQ-7 questionnaire and an increase in the percentage of release of the anal muscles on anorectal manometry. Conclusion: The use of radiofrequency diathermy with a system of static electrodes associated with biofeedback represents a valid rehabilitation option for those patients suffering from anorectal functional pain syndrome because it reduces pain and paradoxical contraction of the levator ani and improves quality of life of the patient.